Studies on the chemistry and biochemistry of gold(III) carboxamide pincer chelates - Razuwika, Rufaro (University of the Witwatersrand, Johannesburg, 2024)
Cancer, a group of diseases characterised by the uncontrollable growth of abnormal or mutated cells within an organ, is a global concern. Metallodrugs have emerged as promising solutions to this pandemic, leading to intense research on different metal complexes. In this study, gold(III) carboxamide pincer complexes were evaluated as potential chemotherapeutic agents. The novel NNN-type carboxamide pincer molecules (ligands) effectively stabilising the gold(III) metal centre. The strong σ-donor properties of both the anionic and pyridine N groups further enhanced this stability. Ligands 1a-1f exhibited atropisomerism, a common feature in drug discovery, and containing special heterocycles such as quinolones, indazole, benzophenone, and phenanthroline, which are particularly relevant in drug development. Atropisomerism, however, was lost upon metalation of the ligands. Three complexes, 2d, 2e, and 2f, were successfully synthesised and isolated. Complex 2d was subjected to biochemical property testing and in vitro analysis due to its superior stability and solubility compared to 2e (poor stability) and 2f (poor solubility in the buffer solution used in the study). Speciation studies, combined with computational studies, suggested that 2d exists as a neutral complex under physiological conditions. This inert complex demonstrated stability against the reducing agent glutathione, indicating resilience to reduction under physiological conditions. DNA spectroscopic titration studies revealed that 2d exhibited intensive interaction with ct-DNA, with binding constants Ka1 = 1.48 x109 M-1 and Ka2 = 6.59 x105 M-1. This interaction resulted in a notable increase in the DNA melting point by 4 °C and an enhancement in viscosity in a dose-responsive manner. The DNA titrations, melting point, and viscosity studies suggested a dual binding mode of 2d to ct-DNA, involving base binding with a nearly equal preference for A, T, G, and C bases, and groove binding. Complex 2d exhibited a high affinity towards the transport protein HSA (Ka values were 1.57 x104 M-1), suggesting that it can be transported in the body by means of the HSA-mediated pathway, enhancing its efficacy and stability. In comparison to its affinity towards DNA, there is a significant difference allowing for the successful transfer of 2d from HSA to DNA. The poor solubility of complex 2d in aqueous environments may have hindered its cellular uptake, but binding to HSA could mitigate this, ensuring minimal interference with its cytotoxicity towards different cancer cell lines. MTT studies demonstrated that 2d has comparable cytotoxicity towards the breast cancer cell line MCF-7 with an IC50 of 9 µM. The IC50 for HT-29 was, however, too high to measure accurately (>100 µM). In conclusion, complex 2d exhibits promising anticancer properties based on its DNA binding studies and cytotoxicity evaluations. This suggests that this class of compounds can be applied in cancer treatments, with potential modifications to compounds 2e and 2f to improve their solubility and stability.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2024
Keywords: Gold(II); Anticancer; Carboxamide pincers; UCTD; SDG-13: Climate action; SDG-4: Quality education